Empirisme Kepuasan Pelanggan Smartphone Oppo yang Ditinjau dari Kualitas Produk dan Harga - Muhammad Abdullah; Brigita Inka Grace Epipanias Larosa; Notia Daeli; Murniwati Laia (Jurnal Manajemen Dirgantara, 2026)
This study examines the simultaneous effects of product quality and pricing on customer satisfaction with Oppo smartphones in Jakarta Pusat, Indonesia. In an increasingly competitive smartphone market, identifying key determinants of customer satisfaction is essential for maintaining brand loyalty and competitive advantage. Utilizing a quantitative causal research design, data were collected from 96 purposively sampled Oppo users residing in Jakarta Pusat. Statistical analysis using SPSS revealed that product quality and price collectively explain 28.3% of the variance in customer satisfaction. Specifically, product durability and biometric feature accuracy positively influenced satisfaction, whereas design aesthetics and ergonomic attributes presented opportunities for enhancement. Price affordability was a significant predictor; however, perceptions regarding value for money were mixed, underscoring the necessity for improved marketing communication. Additionally, customer willingness to recommend Oppo smartphones was identified as an area requiring strategic focus. Based on these findings, practical recommendations include implementing referral incentive programs, targeted social media campaigns to encourage positive user testimonials, and optimizing after-sales services to strengthen brand advocacy and customer retention. This research contributes empirically to the understanding of value-driven satisfaction among urban Indonesian smartphone consumers and offers actionable insights for practitioners seeking to enhance market performance.